The effect of the slow-to-green mutation on cell division during leaf initiation and early leaf growth in Lolium temulentum - Moses, Lynne (The New phytologist, 1997)
Cell division was examined during leaf initiation in the slow-to-green mutant of Lolium temulentum L. to test the hypothesis that the cell cycle in the leaf primordium is a key regulator of the well characterized reduction in final leaf length in the mutant compared with that of the wild type. The cell doubling time (cdt, by colchicine method) was substantially longer in the youngest leaf primordium (YLP) of the mutant (107 h) than in the wild type (43 h) although the duration of the most rapid cell cycle (cc, by percentage labelled mitoses method) was between 18-20 h in each. As a consequence, the proportion of rapidly proliferating cells was only 20 % in the mutant compared with 47 % in the wild type. The size of the shoot apical meristem and the plastochron were similar between genotypes which indicates that the shoot meristem was largely buffered from the effects of the mutation. Mitotic cell area was also similar in the YLP of both genotypes. However, as the leaf elongated, mitotic cell area and interphase cell size were significantly larger in the mutant compared with the wild type. This change was coupled with a reduced number of cells per unit length of leaf in the mutant. The data are consistent in showing that the proportion of rapidly proliferating cells in the YLP (but not the rate of cell division) is a key parameter which influences growth of the leaf